The Eyes Are More Eloquent Than Words: Anticipatory Looking as an Index of Event Memory in Alzheimer's Disease - Hanazuka, Yuki; Futamura, Akinori; Hirata, Satoshi; Midorikawa, Akira; Ono, Kenjiro; Kawamura, Mitsuru (Frontiers in Neurology, 2021)
Alzheimer’s disease (AD) is a disorder in which individuals experience difficulty maintaining event memory for when, where, who, and what. However, verbal deficiency, one of the other symptoms of AD, may prevent precise diagnosis of event memory because existing tests are based on verbal instruction by tester and verbal response from patient. Therefore, nonverbal methods are essential to evaluate event memory in AD. The present study, using eye tracking, investigated whether AD patients deployed anticipatory looking to target acts related to future events based on previous experience when an identical video was presented to them twice. The results revealed presence of anticipatory looking, although participants were unable to verbally report the content of the video. Our results illustrate that AD patients have a one-time event memory better than previously thought.